Sociodemographic, Clinical Variables, and Quality of Life in Patients with Epilepsy in Mekelle City, Northern Ethiopia - Abadi Kahsu Gebre; Amdemicheal Haylay (Behavioural Neurology)
Background. Epilepsy is a chronic neurological disorder characterized by unprovoked recurrent seizure episodes. The disease has detrimental effects on social, cognitive, psychological, and physical components of life consequently quality of life of the patients. The level of the effect of the disease on quality life is influenced by different factors including the use of antiepileptic medications. Objectives. The study was aimed at assessing quality of life in patients with epilepsy and the variables affecting it in Mekelle city, northern Ethiopia. Methods. 175 patients with epilepsy aging 18 years old and above attending neurologic clinics of the two governmental hospitals available in Mekelle city were interviewed using standard and validated Tigrigna version of Quality of Life in Epilepsy Scale-31 (QOLIE-31). One-way ANOVA and independent t-test and analysis of covariance were used for data analysis. Result. The mean age of the patients was 29.36 (standard deviation (SD) 12.77) years old, and 61% of them were males while 52% of the respondents were on phenobarbitone monotherapy. The mean total QOLIE-31 score was 77.97 (SD 20.78) with the highest subscale score for medication effects and the lowest for overall quality of life (QOL) functioning with a score of 86.2 (SD 22.12) and 70.97 (SD 26.43), respectively. The patients with high seizure frequency in the past month before the current visit had a significantly low quality of life 76.81 (SD 21.11). Conversely, patients with tertiary education and above had shown a significantly high quality of life 89.52 (SD 11.85). Conclusion. The overall QOL of the patients was good. Seizure frequency and level of education were found significant predictors of QOL showing the necessity of seizure control and patient education for improving quality of life in patients with epilepsy.